Nominal and real wage flexibility in EMU - Arpaia, Alfonso; Pichelmann, Karl.; European Commission : Directorate-General for Economic and Financial Affairs (Brussels- Belgium: European Comission: Directorate-General for Economic and Financial Affairs, 2007)
Both common macroeconomic shocks and country-specific developments have subjected the flexibility of wage setting mechanisms in the euro area to a stress test in recent years. Against this background, this paper takes a fresh look at wage flexibility in EMU and attempts to draw a few lessons from the experience of the early years. First, we set the stage for the analysis by providing a brief description of the stylised facts regarding nominal and real wage and unit labour cost developments in the euro area over the recent business cycle. Then, the paper presents an empirical assessment of wage inertia based on new econometric estimates of a Phillips-curve type wage equation across euro area countries and offers an interpretation of the main findings with respect to nominal and real wage flexibility. Finally, we investigate the cyclical responsiveness of relative competitive positions among euro area countries. We conclude that from a bird's eye perspective euro area wage and labour cost dynamics have been quite benign in the past couple of years. However, our estimates suggest that persistent cross-country differences in wage and labour cost developments have not always reflected warranted adjustment needs; they are rather indicative of an eventually insufficient degree of nominal and real wage flexibility in the euro area.
Economic Papers